2002
DOI: 10.1038/sj.bjc.6600025
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cell death induced by vinflunine, the most recent Vinca alkaloid in clinical development

Abstract: Vinflunine, the most recent Vinca alkaloid in clinical development, demonstrated superior antitumour activity to other Vincas in preclinical tumour models. This study aimed to define its molecular mechanisms of cell killing in both parental sensitive and vinflunine-resistant P388 leukaemia cells. Vinflunine treatment of these cells resulted in apoptosis characterized by DNA fragmentation and proteolytic cleavage of poly-(ADP-ribose) polymerase. Apoptosis-inducing concentrations of vinflunine caused c-Jun N-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Inactivation of Bcl-2, through hyperphosphorylation (47), leads to mitochondrial membrane permeability and apoptosis triggering by MTDs, including vinflunine (10,11). A relationship has been established between Bcl-2 overexpression and clinical resistance to MTDs (48).…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of Bcl-2, through hyperphosphorylation (47), leads to mitochondrial membrane permeability and apoptosis triggering by MTDs, including vinflunine (10,11). A relationship has been established between Bcl-2 overexpression and clinical resistance to MTDs (48).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, bfl-1 has previously been implicated in chemotherapy resistance development in model systems. Increased expression of bfl-1 has been found in an in vivo established vinflunineresistant murine leukaemia cell line as well as in in vitro established cisplatin-resistant bladder cancer cell lines compared to their respective sensitive parental cell lines (Kruczynski et al, 2002;Kim et al, 2004). We have found that fludarabine did not induce increased bfl-1 expression in B-CLL cells in a short-term culture (Olsson, unpublished observation).…”
Section: Discussionmentioning
confidence: 76%
“…Vinblastine has been modified to vinflunine, which is a novel fluorinated vinca alkaloid. Vinflunine is more efficacious than the parent drug and is undergoing clinical trial [113]. Exatecan, a novel synthetic camptothecin derivative with a unique hexacyclic structure has been synthesized.…”
Section: Modern Therapy Vs Herbal Therapymentioning
confidence: 99%